Evaluation of pregnancy as a risk factor in the outcomes of influenza A (H1N1)/2009 in women of childbearing age Avaliação da gestação como fator de risco nos desfechos da influenza A (H1N1)/2009 em mulheres em idade fértil - Luana Lenzi; Roberto Pontarolo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
The aim of this study was to verify whether pregnancy was a risk factor for death in influenza A (H1N1)/2009 infection. We compared the case-fatality rates for pandemic influenza among non-pregnant women of childbearing age and pregnant women, besides investigating other factors that differentiated the groups in relation to the outcomes. The data were collected from the National Information System on Diseases of Notification (SINAN), of the Ministry of Health. The study used cases with laboratory confirmation and included 1,861 women from 10 to 49 years of age, of whom 352 were pregnant. The case-fatality rate during the 2009 pandemic was 4.5% for pregnant women and 6.4% for non-pregnant women (p = 0.197). Logistic regression did not show an association between pregnancy and death (OR = 0.7; 95%CI: 0.41-1.21). However, there were significant differences between the two groups in relation to mean age, treatment with oseltamivir, schooling, and presence of other risk factors. O objetivo deste estudo foi verificar se a gestação esteve associada como fator de risco para o óbito na infecção por Influenza A (H1N1)/2009. Comparou-se a letalidade da influenza pandêmica entre mulheres em idade fértil e gestantes, realizando ainda a busca por outros fatores que diferenciem os grupos em relação aos desfechos. Os dados foram coletados no Sistema de Informação de Agravos de Notificação (SINAN), do Ministério da Saúde. Foram utilizados os casos confirmados laboratorialmente, sendo incluídas 1.861 mulheres com idades entre 10 e 49 anos, das quais 352 eram gestantes. A taxa de letalidade observada durante a pandemia de 2009 foi de 4,5% para as gestantes e 6,4% para as não gestantes (p = 0,197). O resultado da regressão logística não evidenciou associação entre a presença de gestação e o óbito (OR = 0,7; IC95%: 0,41-1,21). No entanto, houve diferenças significativas entre os dois grupos em relação à idade média, ao tratamento com oseltamivir, à escolaridade e à presença de outros fatores de risco.